A Cross-Sectional Study of 0.6 Million Children with Attention-Deficit/Hyperactivity Disorder in the United States - Rethemiotaki, Irene (Journal of Child Science, 2020)
Attention-deficit hyperactivity disorder (ADHD) is an increasingly recognized chronic neurodevelopmental disorder. This work aims at studying the prevalence and clinical characteristics of children with ADHD in the United States in the period between 2009 and 2018. Data from the National Health Interview Survey were analyzed by univariate and multivariate statistics to assess the role of socioeconomic factors in the development of ADHD. It has been studied 615,608 children, 51.2% male and 48.7% female. The prevalence of ADHD was 9.13%, with males predominating over females. The number of children with ADHD increased from 2009 to 2018 by 14.8%. As specified by multiple logistic regression analysis, males (odds ratio [OR] 2.38) who have neither mother nor father (OR 1.76) are twice as likely to have ADHD compared with their peers. In addition, family income (OR 1.40) and parent's education (OR 1.12) were significantly associated with ADHD. It has been highlighted the significance of deprivation of both family and financial comfort as primary indicators for ADHD in children. Moreover, children with ADHD were more likely to be males in the age group of 12 to 17.
Keywords: ADHD; prognostic factors; socioeconomic factors